Acute Limb Ischemia among COVID-19 Patients in Hospital Kuala Lumpur - Aimanan, Karthigesu; Ali, Nurul Nadiah Nazurah Mohd; Rahman, Mohd Nurhisham Azmi Abdul; Pian, Putra Mas; Pillay, Kumaraguru V.K.; Hayati, Firdaus; Hussein, Hanif (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Acute arterial thromboembolism among the novel coronavirus 2019 (COVID-19) patients is worrying as it can result in significant thrombotic events. AIM: The research aimed to determine the clinical results of COVID-19 infected patients who had ALI (acute limb ischaemia) during the COVID-19 epidemic. METHODS: ALI patients who had a positive COVID-19 were included in the observational cohort study, which was conducted at a single centre. The primary outcomes were 30 days mortality, limb salvage, and successful revascularization. RESULTS: From May to October 2021, data from 21 ALI subjects who had positive COVID-19 were analysed. Of the 21 included subjects, 10 were males (48%). Their mean age was 65±5 years. In nine subjects (42%), revascularization was done. Four (19%) of the 21 persons died while they were hospitalized. Twelve patients underwent major amputation and among them, one patient died after a month of hospitalization for COVID-19-related pneumonia. Among the 12 patients that underwent amputation, 10 of them presented with ALI during the first week of COVID-19 illness. Only one patient developed acute limb ischaemia despite being on heparin thromboprophylaxis. CONCLUSION: Despite attempts at revascularization, ALI-associated with COVID-19 has high mortality and high rates of limb loss. In our experience, major amputation is required in up to a third of patients. This poor result appears to confirm that these infected individuals have a marked hypercoagulable condition. However, adhering to the treatment protocol of heparin thromboprophylaxis confers a benefit in this patient group.